2014
DOI: 10.1016/j.jmb.2014.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Rtr1 Is a Dual Specificity Phosphatase That Dephosphorylates Tyr1 and Ser5 on the RNA Polymerase II CTD

Abstract: The phosphorylation state of heptapeptide repeats within the C-terminal domain (CTD) of the largest subunit of RNA Polymerase II (PolII) controls the transcription cycle and is maintained by the competing action of kinases and phosphatases. Rtr1 was recently proposed to be the enzyme responsible for the transition of PolII into the elongation and termination phases of transcription by removing the phosphate marker on Serine 5, but this attribution was questioned by the apparent lack of enzymatic activity. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
61
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 43 publications
(52 reference statements)
4
61
1
Order By: Relevance
“…In this study, we show that S. cerevisiae Rtr1 is a regulator of Ser5 phosphorylation in the RNAPII CTD in agreement with previous findings (14,39,41,49,51,52). We show that deletion of RTR1 leads to global increases in Ser5-P CTD occupancy at RNAPII target genes, suggesting that Rtr1 is a general regulator of RNAPII phosphorylation during transcription elongation.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…In this study, we show that S. cerevisiae Rtr1 is a regulator of Ser5 phosphorylation in the RNAPII CTD in agreement with previous findings (14,39,41,49,51,52). We show that deletion of RTR1 leads to global increases in Ser5-P CTD occupancy at RNAPII target genes, suggesting that Rtr1 is a general regulator of RNAPII phosphorylation during transcription elongation.…”
supporting
confidence: 92%
“…Ssu72 also participates in gene looping and the suppression of divergent transcription (37,38). Rtr1 is a conserved protein that has been reported by both in vitro and in vivo experimental studies to be a phosphatase responsible for the removal of Ser5-P from the CTD (14,(39)(40)(41)(42). ChIP assays found that the localization of Rtr1 is predominant between the peaks of Ser5-P and Ser2-P.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Rtr1p, (regulator of transcription 1), was previously identified as a phosphatase that dephosphorylates Ser5 and Tyr1 of the RNA polymerase II CTD tail, thus establishing a role for this protein in regulating transcription elongation and termination (Gibney et al 2008;Mosley et al 2009;Hsu et al 2014). In this work we show that Rtr1p autoregulates its own mRNA post-transcriptionally and that this degradation pathway involves the 3 ′ -5 ′ exonucleases Rex2p and Rex3p and the Dhh1p helicase.…”
Section: Introductionmentioning
confidence: 58%
“…Although Ssu72 predominantly regulates S5P-CTD at the 39 ends of genes, it may also act at the 59 end of some genes and can stimulate transcription elongation in vitro (Dichtl et al 2002, Reyes-Reyes and. Another S5P-CTD phosphatase, Rtr1/RPAP2, is implicated to regulate the S5P-S2P transition at gene promoters in yeast (Mosley et al 2009), although the ability of Rtr1 to remove Y1P (Hsu et al 2014) is also consistent with a role in termination. A third candidate, the small CTD phosphatase SCP-1, regulates S5P-CTD levels in the promoter region of neuronal genes (Eick and Geyer 2013).…”
mentioning
confidence: 99%